Bioethics and Physical Medicine: From the Heritage of Asclepius and Hippocrates to the Contemporary Rehabilitation Clinical Practice - Ivet Koleva; Borislav Yoshinov; Julieta Gerenova; Todor Dimitrov; Alexandra Traykovska; Radoslav R. Yoshinov (Current Innovations in Medicine and Medical Science Vol. 7, 2022)
Current article proposes some parallels between the principles of the healing art of the god of Medicine Asclepius, the father of Medicine Hippocrates and the modern medical specialty Physical and Rehabilitation Medicine (PRM). Common principles of Asclepius tradition, Hippocratism and PRM include: application of natural therapeutic factors and methods, holistic approach, objective. In all cases, the goal is functional recovery of the patient and amelioration of his quality of life. The present study sought to investigate the opinion of participants in rehabilitation process (academic staff, rehabilitation team and patients) – concerning their bioethical notions in the rehabilitation field and to realize a comparative evaluation of these perceptions in the early and long-term rehabilitation. Our randomised double-blind study included 105 participants divided into five groups (21 participants per group). All respondents were given a standardised test that covered the principles of the UNESCO Declaration on Bioethics and the List of Bioethical Topics. Many principles of the Declaration on Bioethics are closely related to Asclepius and Hippocrates traditions, as well as concerns of physical medicine and rehabilitation clinical practise, in particular: Human dignity and human rights, Autonomy; Consent; Equality and equity; Non-discrimination and non-stigmatisation (for patients with disability). From the list of bioethical topics, the marked most important issues were: Assisted suicide, Euthanasia, Human research, Neuroethics, Pain management. Patients’ consent, autonomy, human dignity, and research are regarded as the most important elements by members of the academic staff and the staff of PRM Departments. Patients in the early rehabilitation department rated the following as the most important: pain management, the right to use modern treatment and rehabilitation methods and devices, the right to use modern technical aids, and the right to select members of the rehabilitation team. Significant items for patients in the chronic phase were autonomy, home adaptation, the right to proper information, and the right to use contemporaneous treatment methods and devices. Bioethics is considered to be a crucial link between rehabilitation and human values by all respondents. We explain principal parallels between the tradition of Asclepius and Hippocrates and contemporaneous physical medicine.